Catalyst‐Transfer Condensation Polymerization of Acceptor Aromatic Monomers and of Donor Carbon‐Carbon Double Bond‐Containing Monomers. Issue 1 (April 2015) - Yokozawa, Tsutomu; Nanashima, Yutaka; Nojima, Masataka; Ohta, Yoshihiro; Kitayama, Tatsuki; Aoshima, Sadahito; Kamigaito, Masami
Summary Recent developments in catalyst‐transfer condensation polymerization (CTCP), which proceeds in a chain‐growth polymerization manner, have made it possible to synthesize well‐defined π‐conjugated polymers with controlled molecular weight and low polydispersity, as well as block copolymers and gradient copolymers. However, CTCP has been limited to the polymerization of donor monomers (such as thiophene) for the synthesis of p‐type π‐conjugated polymers. Here, we highlight several recent advances in CTCP of acceptor aromatic monomers and monomers conjugated with carbon‐carbon double bond, the π‐donation ability of which is stronger than donor aromatic rings. In the former polymerization, well‐defined poly(pyridine‐3, 5‐diyl), poly(benzotriazole), poly(fluorene‐alt‐benzothiaziazole), and poly(bithiophene‐alt‐naphthalene diimide) were obtained. In the latter polymerization, however, the obtained poly(p‐phenylenevinylene) possessed broad molecular weight distribution.